Diseño de planta desalinizadora de agua de pozo, por medio de osmosis inversa, usando energía fotovoltaica en la comunidad de Poromana, municipio de Manaure (2020)
The objective of this research project is to design a well water desalination plant, using reverse osmosis, using photovoltaic energy in the Poromana Community, Manaure Municipality, thereby seeking to provide an optimal solution to the water problem in said community, which has been suffering from the lack of the precious liquid. This preliminary research project seeks to provide a possible solution to the basic need of this community with a water purification system and to distribute it efficiently to the population.